ANALYSIS OF THE UTILIZATION OF ARTIFICIAL INTELLIGENCE IN THE DIGITAL OFFICE COURSE: A QUALITATIVE STUDY ON OFFICE ADMINISTRATION STUDENTS AT UNIVERSITAS NEGERI JAKARTA - Dinda Ramadhani Qurrota Ayyun; Marsofiyati Marsofiyati; Eka Dewi Utari (Adisam Publisher, 2025)
This study aims to understand the experiences of Office Administration students at Universitas Negeri Jakarta in utilizing Artificial Intelligence (AI) within the Digital Office course. Using a qualitative case study approach, data were collected through interviews with six purposively selected informants. The findings show that students use AI tools such as ChatGPT and Grammarly to complete assignments, generate ideas, and better comprehend learning materials. This utilization has a positive impact on their motivation and learning effectiveness, although challenges such as dependency risks still arise. The study highlights the importance of critical and responsible use of AI in higher education contexts.